How serious are Islamic banks in offering green financing?: an exploratory study on Bangladesh banking sector - Julia, Taslima; Kassim, Salina (Inderscience Enterprises Ltd., 2019)
Development of Bangladesh is endangered because of environmental degradation. Faced with this challenge, the government of Bangladesh introduced green banking policy and encourages banks to participate in offering green financing since 2011. This study aims to examine and compare the green financial performance of selected commercial banks in Bangladesh for three years. In achieving this objective, secondary data is gathered from annual report and green banking report of five conventional banks and five Islamic banks. Additionally, to justify the comparison of Islamic banks performance with conventional counterpart, case study and risk-return analysis is conducted. The study finds that none of the banks fully meet the green policy requirements; however, Islamic banks showed more seriousness than conventional one. To expedite green financing of banks several recommendations are made. Presumably, Islamic banks can contribute more to the sustainable economic growth of the country by in-lining their complete operations with green policies